The Effect of α‐Branched Side Chains on the Structural and Opto‐Electronic Properties of Poly(Diketopyrrolopyrrole‐alt‐Terthiophene) - Saes, Bart W. H. (Chemistry, 2020)
Introducing solubilizing α‐branched alkyl chains on a poly(diketopyrrolopyrrole‐alt‐terthiophene) results in a dramatic change of the structural, optical, and electronic properties compared to the isomeric polymer carrying β‐branched alkyl side chains. When branched at the α‐position the alkyl substituent creates a steric hindrance that reduces the tendency of the polymer to π–π stack and endows the material with a much higher solubility in common organic solvents. The wider π–π stacking and reduced tendency to crystallize, evidenced from grazing‐incidence wide‐angle X‐ray scattering, result in a wider optical band gap in the solid state. In solar cells with a fullerene acceptor, the α‐branched isomer affords a higher open‐circuit voltage, but an overall lower power conversion efficiency as a result of a too well‐mixed nanomorphology. Due its reduced π–π stacking, the α‐branched isomer fluoresces and affords near‐infrared light‐emitting diodes emitting at 820 nm.